An expeditious synthesis of 2, 3‐dihydroquinozoline‐4(1H)‐ones using graphene‐supported sulfonic acid. (9th December 2019) - Gajare, Shivanand; Jagadale, Megha; Naikwade, Altafhusen; Bansode, Prakash; Patil, Pradnya; Rashinkar, Gajanan
Abstract: Graphene‐supported sulfonic acid (Gr@SO3 H) has been prepared by covalent grafting of (3‐mercaptopropyl)trimethoxysilane in the matrix of graphene followed by treatment with sulfuric acid and hydrogen peroxide. Gr@SO3 H has been successfully characterized by Fourier transform infrared (FT‐IR) spectroscopy, Fourier transform Raman (FT‐Raman) spectroscopy, CP‐MAS 13 C NMR spectroscopy, thermogravimetric analysis (TGA), energy dispersive X‐ray analysis (EDX), transmission electron microscopy (TEM), Brunauer‐Emmett‐Teller (BET) analysis, and X‐ray diffractometer (XRD) analysis. Gr@SO3 H served as a robust heterogeneous catalyst for the synthesis of bioactive 2, 3‐dihydroquinazolin‐4(1 H )‐ones from anthranilamide and aryl aldehydes in ethanol. Recyclability experiments were executed successfully for six consecutive runs. Abstract :